Estradiol overcomes adiponectin-resistance in diabetic mice by regulating skeletal muscle adiponectin receptor 1 expression. (15th January 2022) - Chattopadhyay, Sourav; Joharapurkar, Amit; Das, Nabanita; Khatoon, Shamima; Kushwaha, Sapana; Gurjar, Anagha Ashok; Singh, Abhishek Kumar; Shree, Sonal; Ahmed, Md Zohaib; China, Shyamsundar Pal; Pal, Subhashis; Kumar, Harish; et al.
Abstract: Adiponectin and insulin resistance creates a vicious cycle that exacerbates type 2 diabetes. Earlier, we observed that female leptin receptor-deficient BLKS mice (BKS-db/db) were more sensitive to an adiponectin mimetic GTDF than males, which led us to explore if E2 plays a crucial role in modulation of adiponectin-sensitivity. Male but not female BKS-db/db mice were resistant to metabolic effects of globular adiponectin treatment. Male BKS-db/db displayed reduced skeletal muscle AdipoR1 protein expression, which was consequent to elevated polypyrimidine tract binding protein 1 (PTB) and miR-221. E2 treatment in male BKS-db/db, and ovariectomized BALB/c mice rescued AdipoR1 protein expression via downregulation of PTB and miR-221, and also directly increased AdipoR1 mRNA by its classical nuclear receptors. Estrogen receptor regulation via dietary or pharmacological interventions may improve adiponectin resistance and consequently ameliorate insulin resistance in type 2 diabetes. Graphical abstract: Image 1 Highlights: Male but not female BKS-db/db mice are resistant to globular adiponectin treatment. Male BKS-db/db display reduced skeletal muscle AdipoR1 and elevated PTB and miR-221. E2 treatment in male BKS-db/db ameliorates globular adiponectin resistance. Ovariectomy induces adiponectin resistance and estradiol treatment improves it. Estradiol imparts adiponectin sensitivity via its classical nuclear receptors.